Urban Heat Island monitoring with Global Navigation Satellite System (GNSS) data - Mendez-Astudillo, Jorge; Lau, Lawrence; Lun, Isaac Yu Fat; Tang, Yu-Ting; Moore, Terry (Springer, 2020)
The Urban Heat Island (UHI) effect occurs when the temperature in an urban area is higher than the temperature at a rural area. UHIs are monitored using remote sensing techniques such as satellite imagery or using temperature sensors de-ployed in a metropolitan area. In this chapter we propose a methodology to moni-tor the UHI intensity from Global Navigation Satellite Systems (GNSS) data. As the GNSS signal travels from the satellite to the receiver it propagates through the troposphere. A delay (Tropospheric delay) affects the signal. The delay is propor-tional to environmental variables. Also, the tropospheric delay in zenith direction (ZTD) is estimated as part of the Precise Point Positioning (PPP) technique. Therefore, in this chapter it is shown how to use process GNSS data to obtain ZTD and obtain temperature at an urban and a rural site simultaneously from the ZTD. The advantages of using GNSS data is its availability and many GNSS networks have been deployed in different cities so no need to deploy sensor net-works. Furthermore, GNSS signal is less affected by bad weather conditions than satellite imagery.